Low level laser therapy for dentine hypersensitivity - Yui, Karen Cristina Kazue; Cervantes-Jorge, André Luiz; Gonçalves, Sérgio Eduardo Paiva; Rodrigues, José Roberto; Nicoló, Rebeca Di (Brazilian Dental Science, 2010)
Dentine hypersensitivity is a disease that affects both man and women, and it is an overreaction for a stimulusthat normally would not cause pain in a healthy tooth. The etiology is multifactorial, and the pain appearsspecially when the cervical region dentine is exposed to the oral environment. The purpose of this work was totest the efficiency of application of the gallium-aluminum-arsenide diode laser (GaAlAs) in the treatment ofdentine hypersensitivity. Fifty teeth were selected from patients of the São José dos Campos School of Dentistry- UNESP who presented dentine hypersensitivity. The Local Ethics Committee approved this work. The patientswere questioned about pain, and after tactile (probe) and evaporative stimuli (air jet), scores were attributedand recorded in an analogous visual scale: score 10 (unbearable pain); 7 to 9 (strong and bearable pain), 4 to6 (moderate pain), 1 to 3 (light pain) and 0 (no pain). The laser was applied on the surface that presentedsensitivity (non contact) for 2 minutes at 15mW. The scores were attributed before and after each application.No more than 3 applications were performed, with an interval of seven days between them. The results wereanalyzed by the non-parametric Friedman analysis of variance (p